Prevalence of Obesity and Factors Leading to Obesity among High School Students of Pakistan (Journal of Medicine, 2013)
Background: At least 20 million children under the age of 5 years were overweight globally in year 2005. Childhood obesity prevalence has increased by three to four folds globally within past few decades. It is also becoming an important public health problem among Pakistani children due to changes in life style and other factors. This study is aimed to estimate the prevalence of obesity and the associated factors leading to obesity among school students urban city of Hyderabad. Objective: To determine the Prevalence of obesity and factors leading to obesity among high school students of public and private schools of Hyderabad city Pakistan. Methods: A Cross-sectional study was conducted from 01 January 2008 to 30 June 2009 in Hyderabad. A total of 504 male and female students of class six to ten were selected through simple random sampling. They were interviewed by trained data collectors through physical activity and diet questionnaires. Anthropometric measurements were done with calibrated instruments using the age and sex specific BMI cut off points according to WHO growth reference. Data analysis was done on SPSS 16. Results: The prevalence of overweight and obesity was 23% and 15%, respectively, among the boys, while 16% and 8% respectively in girls. When adjusted for other factors multivariate model showed that the girls were protected against obesity, OR=0.33 (0.16-68). Odds ratios for the age groups showed that older children were also protected against obesity. Middle socioeconomic status tertile was more than 3 times more likely to be obese. Conclusions: Childhood obesity is determined by the factors in the home, school and other physical environment and it is recommended that all the stakeholders should take relevant actions for the prevention of the problem.DOI: http://dx.doi.org/10.3329/jom.v14i1.14534 J MEDICINE 2013; 14 : 33-39